Trí tuệ nhân tạo tạo sinh và hiệu quả kinh doanh: Thực nghiệm trong lĩnh vực bán lẻ tại Hà Nội - Lê Xuân, Cù (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The study’s purpose is to analyze the impacts of factors on retailers’ continuance intention toward generative artificial intelligence (GnAI) and their business performance. A research model was extended based on the Motivation - Opportunity - Ability (MOA) theory. A quantitative research method was employed, using a questionnaire to collect data from 325 retailers in Hanoi through a convenience sampling approach. The data were analyzed using structural equation modeling (SEM). The investigations reveal that MOA-related antecedents, including opportunity, ability to use GnAI, and motivations (i.e., hedonic and utilitarian), foster retailers’ continuance intention toward GnAI. Furthermore, the continuance intention boosts GnAI’s retail business performance.. Based on these findings, this work draws several crucial academic and practical implications for strengthening retailers’ perceptions, motivations, abilities, and the sustained utilization of GnAI in retail.